Investigating the relationship between e-learning and mobile learning on students' academic self-handicapping during the outbreak of COVID-19 - Sophia Khaneghahi; Fatemeh Nasripour; Mohammad Aref MahmoudZehi (Journal of Social, Humanity, and Education, 2022)
Purpose: The aim of this study was to investigate the relationship between virtual education and mobile learning on students' academic self-handicapping during the outbreak of COVID19. Research Methodology: The present study is a descriptive study of correlation type. The statistical population includes all primary school students in Zabol city. Using Cochran's formula and Morgan’s table and cluster random sampling method, 277 people were selected as the research sample. Data were collected using the Jones & Rudwalt (1982) Academic Self-handicapping Scale Questionnaire, Mobile Learning Ability Questionnaire, and Virtual Learning Questionnaire. Results: The results of statistical analysis indicate that there is a positive and significant relationship between students’ academic disability and virtual education. The intensity of this relationship is very strong and virtual education has the power to predict academic self-handicapping(P?0.05). Besides that, there is no significant relationship between students’ academic disability and mobile learning. Conclusion: Therefore, we conclude that students who are more prone to academic disability are less likely to participate in the classroom. Limitations: One of the most important limitations of the present study is that due to the timing of the conference, researchers did not have enough time to conduct follow-up tests to sustain the impact of brain teasers.